Effect of soya meat on the quality of beef patties - Islam, MS; Akter, A; Sarker, T; Meem, FT; Hassan, S; Fariha, S; Islam, SS (Meat Research, 2023)
The study was conducted to characterize nutritional, sensory quality and economic feasibility of beef patties as affected by adding soya meat. Therefore, the experiment was conducted with a view to investigate inclusion of soya meat in beef patties with five treatments (T0 = 100% beef; T1 = 75% beef + 25% soya meat; T2 = 50% beef + 50% soya meat; T3 = 25% beef + 75% soya meat and T4 = 100% soya meat) having three replications. The results indicated that adding soy meat to beef patties decreased CP and EE but increased cooking yield and ash. Differences in moisture, CP, EE, ash, CHO, and cooking yield were highly significant (p<0.0001). pH fell in the samples as storage time increased, but increased when soy meat was added and it was found highly significant (p<0.0001) varied. With a high level of soy meat incorporation, L* values increased while a* values decreased. Except for L* values, no discernible variation in the color parameter was found. By using soy meat in beef patties, production costs were reduced. In terms of sensory evaluation, beef patties treated with 50% and 75% soy meat were found to be more acceptable.